2016
DOI: 10.1038/onc.2016.324
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of RAGE-ligand signaling impairs breast cancer cell invasion and metastasis

Abstract: The receptor for advanced glycation end products (RAGE) is highly expressed in various cancers and is correlated with poorer outcome in breast and other cancers. Here we tested the role of targeting RAGE by multiple approaches in the tumor and tumor microenvironment, to inhibit the metastatic process. We first tested how RAGE impacts tumor cell-intrinsic mechanisms using either RAGE overexpression or knockdown with short hairpin RNAs (shRNAs). RAGE ectopic overexpression in breast cancer cells increased MEK-EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
107
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(112 citation statements)
references
References 57 publications
4
107
1
Order By: Relevance
“…Previous experimental studies have revealed that inhibiting RAGE suppressed tumor growth, invasion and angiogenesis in multiple types of cancer (10,16,38). The therapeutic efficacy of blocking RAGE from interacting with HMGB-1 was initially demonstrated in glioma cells, in which this blockade inhibited tumor growth and invasion (16). Subsequently, strategies and components of RAGE inhibition have been reported in oncology and other fields, including neurology (39,40).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous experimental studies have revealed that inhibiting RAGE suppressed tumor growth, invasion and angiogenesis in multiple types of cancer (10,16,38). The therapeutic efficacy of blocking RAGE from interacting with HMGB-1 was initially demonstrated in glioma cells, in which this blockade inhibited tumor growth and invasion (16). Subsequently, strategies and components of RAGE inhibition have been reported in oncology and other fields, including neurology (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, blocking RAGE and ligand-RAGE signaling could represent a potential strategy for treating certain types of cancer. Previous experimental studies have revealed that inhibiting RAGE suppressed tumor growth, invasion and angiogenesis in multiple types of cancer (10,16,38). The therapeutic efficacy of blocking RAGE from interacting with HMGB-1 was initially demonstrated in glioma cells, in which this blockade inhibited tumor growth and invasion (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because research has implicated inflammation and leukocyte recruitment in breast cancer progression, next, the same investigators explored whether SM‐related changes in leukocyte transcriptional activities during primary treatment could explain the effects of CBSM on increased the time to recurrence in this cohort. To examine whether the immunologic changes observed after CBSM over the initial 12 months of primary treatment predicted 11‐year disease‐free survival, the investigators used a 53‐gene composite, including 19 proinflammatory transcripts and 34 transcripts (inversely scored) related to type I IFN responses and antibody synthesis, based on prior research on stress and adversity .…”
Section: Sm and The Immune Processes In Patients With Cancermentioning
confidence: 99%